2021
DOI: 10.1093/neuopn/okab004
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Dose-Response and Risk Factors for Obliteration of Arteriovenous Malformations Following Radiosurgery: An Update Based on the Last 20 Years of Published Clinical Evidence

Abstract: BACKGROUND Intracranial arteriovenous malformation (AVM) is a congenital lesion that can potentially lead to devastating consequences if not treated. Many institutional cohort studies have reported on the outcomes after radiosurgery and factors associated with successful obliteration in the last few decades. OBJECTIVE To quantitatively assess the dose-response relationship and risk factors associated with AVM obliteration usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…SRS is currently used to treat patients with a variety of processes including cerebral vascular malformations (arteriovenous malformations or AVMs [ 15 ] and cavernous angiomas [ 16 ]), benign tumors (meningiomas [ 17 - 18 ], vestibular schwannoma [ 19 ], pituitary adenoma [ 20 - 21 ], glomus jugulare tumors [ 22 ], low-grade glioma [ 23 ]), and malignant tumors (metastasis [ 24 ], chordoma [ 25 ], high-grade glioma [ 26 ]). Other less common indications are Cushing's disease [ 27 - 28 ], epilepsy [ 29 ], trigeminal neuralgia [ 30 ], and movement disorders [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…SRS is currently used to treat patients with a variety of processes including cerebral vascular malformations (arteriovenous malformations or AVMs [ 15 ] and cavernous angiomas [ 16 ]), benign tumors (meningiomas [ 17 - 18 ], vestibular schwannoma [ 19 ], pituitary adenoma [ 20 - 21 ], glomus jugulare tumors [ 22 ], low-grade glioma [ 23 ]), and malignant tumors (metastasis [ 24 ], chordoma [ 25 ], high-grade glioma [ 26 ]). Other less common indications are Cushing's disease [ 27 - 28 ], epilepsy [ 29 ], trigeminal neuralgia [ 30 ], and movement disorders [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 A large meta-analysis of radiosurgery for AVMs found that obliteration rates are most favorable for smaller AVMs (even at lower doses) and compact nidi in addition to several other factors. 14 The risk of repeat hemorrhage during the time to obliteration following treatment must be considered in the management of micro-AVMs. Friedman et al reviewed outcomes in 201 patients with AVMs treated with radiosurgery and discovered that the annual risk of postoperative hemorrhage is 3.7% within 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…For VS-SRS, a gamma knife is basically used, and the mean marginal dose varies from 15 to 20 Gy, and the number of stages of irradiations is often reported to be two to four stages [ 14 , 15 ]. For dose staged SRS, a linear accelerator (LINAC) is used, and the mean total dose varies from 26 to 50 Gy, and the number of stages of irradiation varies from two to 12 stages [ 16 , 17 ]. The mean complete occlusion rate was 32.3% for DS-SRS and 41.2% for VS-SRS [ 15 ].…”
Section: Discussionmentioning
confidence: 99%